Pengaruh Penambahan Tepung Pisang pada Pembuatan Kerupuk - Yasin, Novita (Universitas Gorontalo, 2018)
crackers is the product dry food that has been known in Indonesia, food spread almost to all corners of Indonesia and favored by all walks of life. one of the type of banana that can be used as flour banana is banana kepok. flour banana made of bananas still raw but that was old enough. utilization of flour bananas in the substitution making food items are expected to reduce the dependence of wheat flour. the purpose of penelitin this is to obtain the formulation of the appropriate for the manufacture crackers with a basic materials flour banana kepok and to know the revenue panelists to the characteristics crackers flour banana kepok. this study was conducted in the laboratory technology agricultural University gorontalo and laboratory technology agricultural Polytechnic gorontalo. this research was conducted in the form of the design of randomized complete (RAL) consisting of 3 treatment and 3 times replicates. parameters conducted in this study is water content, ash content, level of carbohydrate and test organoleptic. treatment of research influential very real at the level of carbohydrate, ash content and water content. based test results organoleptic, treatment is best a2 (50% tapioca starch + 50% of flour banana kepok) with a score of aroma 2,9 (somewhat like), a sense of 3,0 (like), texture 2,8 (somewhat like) and the color of 2,7 (somewhat like) grading carbohydrates 8,83%, water content 8,48% and ash content 2,42%.Â Keywords : crackers, flour banana kepok, banana kepok, test organoleptic, test proximate